Anodic oxidation of anti-cancer drug Imatinib on different electrodes: Kinetics, transformation by-products and toxicity assessment. (10th February 2018) - Turkay, Ozge; Barışçı, Sibel; Ulusoy, Ebru; Şeker, Mine Gül; Dimoglo, Anatoli
Abstract: Degradation of anti-cancer drug Imatinib (IMT) in aqueous solution by anodic oxidation at different electrodes, namely Ti/RuO2, Ti/Pt, Ti/IrO2 RuO2, Ti/Ta2 O5 SnO2 IrO2, Ti/IrO2 Ta2 O5 SnO2 /Pt and boron doped diamond (BDD), has been investigated. The effect of the applied current density and initial pH of the solution were examined. The electron structure calculations has been calculated by density functional theory (DFT). These results were compared to the results of liquid chromatography-mass spectroscopy (LC-MS-MS) and the metabolites has been identified. Moreover, the toxicity behavior of treated IMT solution by Ti/RuO2 and BDD electrodes were clarified and compared. IMT degradation was in the order of Ti/RuO2 >Ti/Pt > Ti/IrO2 Ta2 O5 >Ti/Ta2 O5 SnO2 IrO2 >Ti/IrO2 RuO2 >SnO2 /Pt > BDD. At the initial stage of the IMT degradation, fragments with molecular weights 394 and 100 g mol −1 are formed. As a result of further degradation, the metabolites with m / z  = 394 g mol −1 and m / z  = 222 g mol −1 were formed. The bond NHC/O breakup may happen with the appearance of fragments having molecular weights 217 and 277 g mol −1 . Experimental exploration of the metabolites has been also confirmed by the LC-MS-MS. EC50 value of IMT solution was determined as 2.50 mg L −1 . Toxicity of BDD treated solution was significantly higher than Ti/RuO2 treated solution at the end of the process. This study demonstrates that anodic oxidation of IMT could be applied for the degradation of such anti-cancer drugs in wastewater treatment. Considering the toxicity behavior of treated IMT solutions, the usage of Ti/RuO2 as anode was the most effective one together with its oxidation capacity. Graphical abstract: Highlights: The most effective anode was found as Ti/RuO2 with 99% degradation efficiency. Increase in current density from 15 mA cm −2 to 30 mA cm −2 enhanced IMT degradation. The degradation rates were slower in acidic and alkaline medium. DFT calculations and LC-MS-MS analysis have been conducted to identify intermediates. Toxicity of BDD treated solution was significantly higher than Ti/RuO2 treated solution.